The mosque : the heart of submission - Mahmutćehajić, Rusmir, 1948- (Abrahamic dialogues series, 2006)
Argues that the mosque is not an analogue of the Christian church. Rather, every Muslim is his or her own priest, and most religious obligations are performed in the home. This book seeks to rebuild the spirit and majesty of each mosque that was destroyed.